Criminal Liability of Business Actors Who Do Not Have A Mining Permit for Non-Metallic Minerals and Rocks Case Study in Asahan Regency - Pranoto, Agus; Kusbianto, Kusbianto; Sitompul, Ariman (Jurnal Ilmiah Global Education, 2025)
This study discusses legal aspects, forms of sanctions, as well as efforts to recover and prevent violations in mining activities of non-metallic minerals and rocks (MBLB) in North Sumatra province. Based On The North Sumatra Regional Regulation No. 2 year 2013, businesses must have a license to carry out mining activities to ensure sustainable governance. Non-compliance with this regulation resulted in negative impacts including environmental damage, social conflicts, and loss of local revenue potential. In law enforcement, the sanctions applied include criminal penalties in the form of imprisonment and fines, along with the obligation to restore the environment by business actors. Enforcement proceedings also involve investigation, seizure of evidence, as well as supervision of the execution of court decisions.The research method used is normative juridical approach with qualitative analysis.The results showed that the success of mine governance depends on the synergy between adaptive regulation, consistent law enforcement, and active participation of all stakeholders. The use of modern technology and regular regulatory evaluation are also key to improving the effectiveness of surveillance and Prevention of violations. With an integrated approach, the mining sector of non-metallic minerals and rocks is expected to provide sustainable economic benefits without compromising environmental sustainability and community welfare. This study recommends strengthening the capacity of law enforcement officials, increasing transparency, and regulatory education to business actors as strategic steps to prevent violations in the future.